Lysinibacillus sphaericus plant growth promoter and lead phytoremedation enhancer with Canavalia ensiformis (2017)
Lysinibacillus sphaericus is known for its great larvicidal activity against mosquito larvae and toxic metal resistance, but knowledge about its possible activity in soil is scarce and poor. Nevertheless, the genome of some strains that have been reported (CBAM5, and OT4b.31) revealed genes of nitrogen cycle. Seven L. sphaericus strains were tested as nitrogen fixing bacteria, nitrifying bacteria, and indole acetic acid producer. Subsequently a consortium was formulated using the best strains (CBAM5, III(3)7, OT4b.31 and OT4b.49) to evaluate its effect in Canavalia ensiformis growth and lead phytoremediation. All L. sphaericus strains were able to fix nitrogen (0,61-1 ,47mg/L of ammonium), nitrify (0,26-0,7mg/L of nitrate) and produce IAA (3,3-5.5 æg/mL in L-tryptophan media and 0,3-1 ,1æg/mL in trypticase broth). They also promoted shoot length, root length, foliar area and leaf number in C. ensiformis, enhanced lead bioaccumulation in the root reaching a removal of 40% of lead in greenhouse experiment, and increased nitrate content in soil 2 fold in contrast to the control in field experiment. We therefore believe that Lysinibacillus sphaericus could be a key organism in the formulation of biofertilizers, as it shows potential in the phytoremediation processes and in crop plant nutrition, and growth in low nutrient polluted soils, then is a Plant Growth Promoter Bacteria (PGPB).